Introduction of A Time for Recommitment: Building the New Relationship between Christians and Jews - Cunningham, Philip A. (Studies in Christian-Jewish Relations, 2011)
A founding officer and secretary-treasurer of The Council of Centers on Christian-Jewish Relations, Dr. Philip A. Cunningham, addressed the assembly at the July 2009 Berlin ICCJ conference before the ceremony at which representatives from twenty-three countries signed the 'A Time for Recommitment' document.